2012
DOI: 10.1007/s10802-012-9656-1
|View full text |Cite
|
Sign up to set email alerts
|

Linking Childhood Sexual Abuse and Early Adolescent Risk Behavior: The Intervening Role of Internalizing and Externalizing Problems

Abstract: A robust literature links childhood sexual abuse (CSA) to later substance use and sexual risk behavior; yet, relatively little empirical attention has been devoted to identifying the mechanisms linking CSA to risky behavior among youth, with even less work examining such processes in boys. With the aim of addressing this gap in the literature, the current study examined the indirect effect of childhood sexual abuse (CSA; from age 2 to 12) trajectory group on risky behavior at age 14 (alcohol use & sexual inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 83 publications
6
47
2
1
Order By: Relevance
“…The association between trauma type and RSB depends on gender in that sexual trauma was associated with RSB for females but physical trauma was associated with RSB for males. These results were consistent with Jones et al (2013). The moderating effect of gender on the relationship between trauma type and RSB shows that males and females have different psychological responses to different trauma experiences.…”
Section: Variablesupporting
confidence: 84%
See 1 more Smart Citation
“…The association between trauma type and RSB depends on gender in that sexual trauma was associated with RSB for females but physical trauma was associated with RSB for males. These results were consistent with Jones et al (2013). The moderating effect of gender on the relationship between trauma type and RSB shows that males and females have different psychological responses to different trauma experiences.…”
Section: Variablesupporting
confidence: 84%
“…Physical abuse by a romantic partner also predicted the use of alcoholand substances priortoengagementin sexualactivity.Their study, however, did not clearly define sexual abuse. Jones et al (2013) found that physical abuse was positively associated with RSB among boys and CSA was positively associated with RSB amonggirls,suggestingthatthetypeoftraumaassociatedwithRSB depends on the sex of the individual. They also found that these relationshipswerenotmediatedbydepression.Intotal,thesestudies suggest that other traumatic experiences in addition to childhood sexual abuse may predict RSB.…”
Section: Introductionmentioning
confidence: 93%
“…This is particularly important because distress and externalizing problems have been associated with risk-taking behaviors among youth. [64][65][66] Although mean externalizing scores did not differ by family history group, a higher percentage of 10-to 13-year-old BCFH+ girls met clinical cutoffs. It will be important to understand the mediators of psychosocial adjustment and the impact on health and risk behaviors over time.…”
Section: Discussionmentioning
confidence: 84%
“…Most research in the United States has relied on adults' memories of childhood sexual victimization (Goodman et al, 2010;Lindblom & Gray, 2010). Extensive literature has investigated CSA and problematic behaviors in adults (e.g., substance abuse and high risk sexual behaviors), yet substantially less research has focused on children and adolescents (Jones et al, 2013). However, there are a few studies in the U.S. that have used child victims themselves as the primary sources of information about CSA.…”
Section: Introductionmentioning
confidence: 99%